Citizen Journalism as alternative practices for Dakwah Purposes - Andini Nurbahri (Jurnal Komunika Islamika : Jurnal Ilmu Komunikasi dan Kajian Islam, 2019)
Nowadays people can publish important news actively through their social media and their participation in that news process changed the definition of news consumers into citizen journalism. Citizen journalism is no longer just about overcoming the limits of journalistic professionalism, it goes further and tries to overcome the imbalance of the mainstream media in informing and sharing the news related to da’wah interest for Muslim. This article examine the role and challenge of citizen journalism as the alternative practice for Da’wah purposes